Antidiabetic drugs and the risk of cancer: beneficial, neutral, or detrimental? - Azeez Taoreed Adegoke; Folorunso Sharif Adeniyi; Eguzozie Chinedu; Adegboyega Adeleke Adedapo (Forum of Clinical Oncology)
The prevalence of diabetes mellitus is rapidly rising, especially in low- and middle-income countries. Also, early-onset diabetes is on the rise, and millions of individuals have to be on antidiabetic medications for a prolonged period. Therefore, more people are getting exposed to the adverse effects of antidiabetic medications.